META ANALISIS HUBUNGAN GANGGUAN KOGNITIF DENGAN RESIKO JATUH PADA LANSIA - Abida, Liza Laela; Pambudi, Restu Arya; Kurniawan, Ganesa P.D. (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Cognitive function will decline with age. This is due to neurobiological aging, this will affect balance and thus influence the risk factors for falls in the elderly. Method: This study used a systematic review and meta-analysis with PICO (population: elderly, intervention: cognitive impairment, comparison: non-cognitive impairment, outcome: risk factors for falls in the elderly). Results: There is a relationship between cognitive impairment and the risk of falls in the elderly with AOR: 1.17 (1.11 to 1.23) with p < 0.00001. Keywords: cognitive impairment,risk fall, elderly.